The Use of Directive Speech Acts in Piratengold, A German Translated Donald Duck Comics - Ovy Haniffauzi Zahid Santoso; Iman Santoso (LACULTOUR: Journal of Language and Cultural Tourism, 2023)
This study aims to describe (1) the form of directive speech act, and (2) the function of directive speech in a German-translated comic Donald Duck by Carl barks. The subject of this research is a German translation comic Donald Duck by Carl Barks with the sub-title Piratengold story. The object of this research is all forms and functions of directive speech act contained in Piratengold. This research design is descriptive qualitative, data collection techniques in this research with reading and note techniques, while data validity testing with repeated reading and expert judgement. The method used to analyze directive speech act in Piratengold comics is padan pragmatis method. The results of this study show that (1) the form of directive speech in Piratengold comic has three forms of speech, namely literal direct speech with 111 data, literal indirect speech with 25 data, and non-literal direct speech with five data. (2) There are six functions of directive speech act in Donald Duck comic, namely the request function with 12 data, the question function with 17 data, the command function with 89 data, the prohibition function with 7 data, the permission function with 7 data, and the advice function with 8 data.